x(x+6)=9x+10

Simple and best practice solution for x(x+6)=9x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+6)=9x+10 equation:



x(x+6)=9x+10
We move all terms to the left:
x(x+6)-(9x+10)=0
We multiply parentheses
x^2+6x-(9x+10)=0
We get rid of parentheses
x^2+6x-9x-10=0
We add all the numbers together, and all the variables
x^2-3x-10=0
a = 1; b = -3; c = -10;
Δ = b2-4ac
Δ = -32-4·1·(-10)
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{49}=7$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-7}{2*1}=\frac{-4}{2} =-2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+7}{2*1}=\frac{10}{2} =5 $

See similar equations:

| 85y=14(6y+31) | | 65=3t-16t | | 5x+20+5x+10x-30+3x+2=360 | | 4x+244=14x-6 | | 28-5x=14-8x | | x(x+6)=8x+24 | | 3/5(x+15)=66 | | 9x-50+2x+10=180 | | 28x+46x=259 | | 15=16t+4.9t^2 | | 5·x-50=x+2 | | -6-7=-9+y | | 6/5=x+2/3 | | 3(4x+6)-8x=62 | | 6x-11/22=1 | | 4t-9=(t+5) | | 10x+35=5x+5 | | 7p+7=-28 | | ×-4y=2 | | X=5x-150 | | 5x-10°=170 | | 8x-28=x-21 | | X/2+1/6=x-1/3 | | X÷2+1/6=x-1/3 | | 5x+25=11x+1 | | |y|=5 | | 1/3x-5+23=x | | 4x+x+29=106.5 | | 8x+21=64 | | 5x+3(×+40)=0 | | X²-18x+10=0 | | f(2)=4-6 |

Equations solver categories